Ojcowska żałoba Karola Irzykowskiego - Kraskowska, Ewa (Wydawnictwo IBL, 2008)
This article deals with a relatively not-too-well-known text by Karol Irzykowski, composed of fragments of the writer s diary devoted to the sickness and death of his five-year- -old daughter Basia. Irzykowski took down his notes as things went on, trying his best at possibly most sincerely evidencing individual phases of that traumatic experience as well as his own feelings triggered by it. Ms. Kraskowska analyses Irzykowski s notes in a gender perspective, asking questions on cultural conditioning of mourning. She moreover juxtaposes these with Pa³uba, the novel published dozen-or-so years earlier, in which the themes of illness, death and mourning take an essential part. To the scholar s mind, Irzykowski although driven he was by an imperative of sincerity was experiencing the events related to the loss of his little girl in a manner resembling that of a scenario projected for a novel s purposes.
Karol Irzykowski’s Fatherly Mourning
Keywords: żałoba; ojcostwo; Karol Irzykowski